A Reciprocal Link Between Gut Microbiota, Inflammation and Depression: A Place for Probiotics? - Eltokhi, Ahmed; Sommer, Iris E. (Frontiers in Neuroscience, 2022)
Depression is a severe mental disorder that places a significant economic burden on public health. The reciprocal link between the trillions of bacteria in the gut, the microbiota, and depression is a controversial topic in neuroscience research and has drawn the attention of public interest and press coverage in recent years. Mounting pieces of evidence shed light on the role of the gut microbiota in depression, which is suggested to involve immune, endocrine, and neural pathways that are the main components of the microbiota-gut-brain axis. The gut microbiota play major roles in brain development and physiology and ultimately behavior. The bidirectional communication between the gut microbiota and brain function has been extensively explored in animal models of depression and clinical research in humans. Certain gut microbiota strains have been associated with the pathophysiology of depression. Therefore, oral intake of probiotics, the beneficial living bacteria and yeast, may represent a therapeutic approach for depression treatment. In this review, we summarize the findings describing the possible links between the gut microbiota and depression, focusing mainly on the inflammatory markers and sex hormones. By discussing preclinical and clinical studies on probiotics as a supplementary therapy for depression, we suggest that probiotics may be beneficial in alleviating depressive symptoms, possibly through immune modulation. Still, further comprehensive studies are required to draw a more solid conclusion regarding the efficacy of probiotics and their mechanisms of action.